2009
DOI: 10.1136/hrt.2008.158915
|View full text |Cite
|
Sign up to set email alerts
|

Late benefits of dual-chamber pacing in obstructive hypertrophic cardiomyopathy: a 10-year follow-up study

Abstract: Pacing in HCM results in a significant reduction in obstruction, improvement of symptoms and exercise capacity that is progressive and may be achieved after a long period of time. In this series, only 18% of cases needed a more aggressive treatment to relieve residual obstruction and obtain a satisfactory symptomatic status. In conclusion, these results emphasise the need for new controlled studies of pacing with a longer follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 27 publications
4
34
0
5
Order By: Relevance
“…There are some reports showing that the pressure gradient of HOCM is ameliorated by dual chamber pacing with short atrioventricular delay, which leads to LV dyssynchronous contraction. 5,6) In this regard, LV dyssynchrony might be required to relieve the LVOT pressure gradient of HOCM. We present a patient with both WPW syndrome and HOCM in whom the LVOT pressure gradient was affected by RFA.…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports showing that the pressure gradient of HOCM is ameliorated by dual chamber pacing with short atrioventricular delay, which leads to LV dyssynchronous contraction. 5,6) In this regard, LV dyssynchrony might be required to relieve the LVOT pressure gradient of HOCM. We present a patient with both WPW syndrome and HOCM in whom the LVOT pressure gradient was affected by RFA.…”
Section: Discussionmentioning
confidence: 99%
“…Zmniejszenie zawężenia drogi odpływu lewej komory i niespójny wpływ na objawy i jakość życia wykazano w 3 małych randomizowanych, kontrolowanych placebo badaniach z zastosowaniem trybu DDD wobec stymulacji AAI w obserwacyjnych badaniach długoterminowych [143][144][145][146][147][148]. Zasadniczo redukcja gradientu jest również mniejsza niż po operacji lub po ablacji alkoholowej przegrody.…”
Section: Stymulacja W Kardiomiopatii Przerostowej Bradyarytmiaunclassified
“…DDD pacing is a reasonable alternative to surgery in symptomatic children despite pharmacological treatment if they are still too young for surgery, taking into account that the approach to an extended septal myectomy is just the aortic valve with a small annulus at this age. A very recent study has also shown progressive relief of symptoms and gradient reduction at long term follow-up (Galve et al, 2010). However, as with other types of treatment, DDD pacing does not protect against the possibility of sudden arrhythmic death (Bruno et al, 2002).…”
Section: Treatmentmentioning
confidence: 99%